2015
DOI: 10.1002/2015jd023853
|View full text |Cite
|
Sign up to set email alerts
|

Multimodel ensemble projection of precipitation in eastern China under A1B emission scenario

Abstract: As part of the Regional Climate Model Intercomparison Project for Asia, future precipitation projection in China is constructed using five regional climate models (RCMs) driven by the same global climate model (GCM) of European Centre/Hamburg version 5. The simulations cover both the control climate and future projection under the Intergovernmental Panel on Climate Change emission scenario A1B. For the control climate, the RCMs have an advantage over the driving GCM in reproducing the summer mean precipitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 64 publications
1
31
0
Order By: Relevance
“…Uncertainty in projected climate change mainly arises from the internal variability of the climate system, the model uncertainty, and the scenario uncertainty (Niu et al, 2015;Woldemeskel et al, 2016). In this study, all RCMs are driven by the same GCM under the same scenario, and thus, the uncertainty of the climate projections is mainly caused by inter-RCM and internal variability.…”
Section: Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncertainty in projected climate change mainly arises from the internal variability of the climate system, the model uncertainty, and the scenario uncertainty (Niu et al, 2015;Woldemeskel et al, 2016). In this study, all RCMs are driven by the same GCM under the same scenario, and thus, the uncertainty of the climate projections is mainly caused by inter-RCM and internal variability.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…go.kr/cordex/download.do, last access: 18 May 2018). A series of studies based on RCMs within CORDEX-EA has been conducted to project extreme and mean precipitation and temperature in East Asia (Jin et al, 2016;Lee et al, 2014;Niu et al, 2015;Park et al, 2016;Tang et al, 2016;Um et al, 2017), but little attention has been paid to quantify the contributions of the uncertainty in future climate projection over China.…”
Section: H Gu Et Al: Ensemble Future Climate Projections and Uncertmentioning
confidence: 99%
“…Niu et al . () constructed future precipitation in China using five RCMs driven by the one GCM, and found that similar changes in summer precipitation were projected by all RCMs over western China, but model behaviours were quite different over eastern China of the Eastern Asian Summer Monsoon region.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic studies have been performed to quantify and reduce the uncertainties in the regional climate projections (e.g. Déqué et al, 2007;Marengo et al, 2010;Gao et al, 2012a;Wang et al, 2014;Niu et al, 2015;Wu and Huang, 2016). In China, significant contributions of driving GCMs to the uncertainties in precipitation change were detected by Gao et al (2012a), using one RCM to downscale multi-GCMs for the precipitation change projections.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, all RCMs are driven by the same GCM under the same scenario, so the uncertainty of the climate projections is mainly caused by the inter-RCM variability and internal variability (Niu et al, 2015). The method developed by Hawkins 25 and Sutton (2009; was used for separating these two sources of uncertainty.…”
Section: Analysis Methods 20mentioning
confidence: 99%